Earth verse : haiku from the ground up - Walker, Sally M. (Candlewick Press, 2018)
A collection of haiku poems celebrates the planet Earth, including such topics as rocks, earthquakes, fossils, volcanoes, and the water cycle. Includes Earth sciences fact pages.